ANALYSIS OF THE CURRENT SITUATION AND ABSORPTION OF FOREIGN INVESTMENTS ATTRACTED TO SMALL BUSINESS SECTORS IN NAMANGAN REGION - Sarybaeva Azadajan Baratbaevna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
In this article, the analysis of the current situation and absorption of foreign investments attracted to small business sectors in Namangan region and the prospects of effective use of the favorable investment environment in attracting foreign investments are presented.